Dampak Kebersihan Lembaga Pemasyarakatan Terhadap Psikologis Narapidana Pada Lembaga Pemasyarakatan Kelas II B Ngawi - Waskito Galang Estu Wicaksono; Ali Muhammad (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research aims to explore the impact of cleanliness on prisoners' psychology. When serving a sentence in a correctional institution, hygiene conditions can affect the psychological well-being of prisoners. The method used in this research is interviews with prisoners and data analysis to evaluate the relationship between the cleanliness of correctional institutions and the psychological well-being of prisoners. The results of this research indicate that improving cleanliness at the Class II B Ngawi Penitentiary can improve the psychological well-being of prisoners. The conclusion of this research is the importance of maintaining cleanliness in correctional institutions as an effort to improve the psychological well-being of prisoners. This research has important implications in efforts to rehabilitate prisoners and improve the correctional system.